Benin : Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report, 2005)
The Poverty Reduction Strategy Papers (PRSPs) on Benin analyzes poverty trends and economic policies. The gap between the Millennium Development Goals (MDGs) poverty line and trends recorded in Benin is still considerable, especially in terms of the depth and gravity of poverty. Progress on good governance and institutional capacity building was uneven. To achieve the overall and sectoral targets set by the PRSP, additional funds must be mobilized for implementing the final phase. It will also be important to start reflecting on the next PRSP, including a plan to evaluate implementation.